Joint analysis of water rights trading and water-saving management contracts in China. Issue 4 (3rd July 2020) - Guo, Hui; Chen, Xiangdong; Liu, Jiahong; Zhang, Hongjiang; Svensson, Jesper
ABSTRACT: Water rights trading and water-saving management contracts are important market-oriented means to promote water conservation. This study integrates them together for a joint analysis, and puts forward a new way to optimize market-oriented water-saving services in China. This is to establish a water-saving management contracts-based water rights trading mechanism, that is, to allow trading of water saved under a management contract. We have two main findings. First, water-saving management contracts and water rights trading are highly compatible and interrelated. Second, water rights trading can be integrated into the implementation of water-saving management contracts and thereby promote their application.